2003
DOI: 10.1074/jbc.m301744200
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-xL Mediates a Survival Mechanism Independent of the Phosphoinositide 3-Kinase/Akt Pathway in Prostate Cancer Cells

Abstract: Among various molecular strategies by which prostate cancer cells evade apoptosis, phosphoinositide 3-kinase (PI3K)/Akt signaling represents a dominant survival pathway. However, different prostate cancer cell lines such as LNCaP and PC-3 display differential sensitivity to the apoptotic effect of PI3K inhibition in serum-free media, reflecting the heterogeneous nature of prostate cancer in apoptosis regulation. Whereas both cell lines are equally susceptible to LY294002-mediated Akt dephosphorylation, only LN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

2004
2004
2007
2007

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 58 publications
(49 citation statements)
references
References 28 publications
5
43
1
Order By: Relevance
“…Celecoxib induced apoptosis in the prostate cancer cell line also appears to be independent of Bcl-2. 29,30,32 The protection of mitochondrial membrane potential by CsA together with the noninvolvement of Bcl-2 in our oral cell lines suggests that the celecoxib derivatives modulate signaling pathways bypassing Bcl-2 or interact with the mitochondria membrane to induce apoptosis. 26 Further studies are needed to identify and decipher the targets, mechanisms and interactions between pathways which lead to celecoxib derivative induced apoptosis in different cancer phenotypes.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Celecoxib induced apoptosis in the prostate cancer cell line also appears to be independent of Bcl-2. 29,30,32 The protection of mitochondrial membrane potential by CsA together with the noninvolvement of Bcl-2 in our oral cell lines suggests that the celecoxib derivatives modulate signaling pathways bypassing Bcl-2 or interact with the mitochondria membrane to induce apoptosis. 26 Further studies are needed to identify and decipher the targets, mechanisms and interactions between pathways which lead to celecoxib derivative induced apoptosis in different cancer phenotypes.…”
Section: Discussionmentioning
confidence: 92%
“…26 Studies in human prostate cancer cell lines indicate that celecoxib induces apoptosis by blocking Akt and Erk2 activation, through the mitochondrial pathway, independent of COX-2 activity and Bcl-2. 8,29,30 This has led to the design of celecoxib derivatives that optimize the apoptosis-inducing potency, separate from the COX inhibiting activity of celecoxib. 8,[31][32][33] Recent studies with the first and second generation derivatives of celecoxib in the PC-3 human prostate cell line suggests that apoptosis is mediated through the blockade of Akt activation by derivative inhibition of 3-phosphoinositide dependent kinase-1 (PDK1).…”
mentioning
confidence: 99%
“…Cytosolic-specific, mitochondria-free lysates were prepared as described in Miyake et al [30]. After 48 h adenovirus infection, Ho-8910 cells were collected by centrifugation at 600 × g for 5 min.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…These preliminary results indicated that viability was severely reduced in cells ectopically expressing either CT or CTsv. In order to assess whether this phenomenon may be due to apoptosis we monitored the cells with an ELISA technique which detects the enrichment of mono-and oligonucleosomes in the cytoplasm of the transfected cells (13). Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These can be detected by an ELISA assay that is quite sensitive and specific for apoptosis (13). Transfected HeLa cells were gently lysed to release mono-and oligo-nucleosomes from apoptotic cells.…”
Section: Cell Death Elisa Detectionmentioning
confidence: 99%